Learning Models, Motivation and Literacy as Intervening That Influence Learning Interest - Purwanta, Jaka; Sudigdo, Agus (Universitas Pamulang, 2023)
The learning model, learning motivation, and mathematical literacy have a large influence on learning interests in Budiniah Vocational High School students. This study aims to analyze the effect of the learning model variable, learning motivation on learning interest which is intervened by the mathematical literacy variable in students at Budiniah Citeureup Vocational School. This study used a sample of 80 class XI students at SMK Budiniah Citeureup Bogor using a Path Analysis model with a 5% margin of error. Data collection techniques with observation and questionnaire methods. In data processing using the SPSS application with data testing, among others, validity test, reliability test and classical assumption test. In this study it was concluded that the learning model.